GAMBARAN STATUS GIZI DAN TINGKAT PENGETAHUAN IBU DI DESA PERAPAKAN KECAMATAN PEMANGKAT - M. Daffa Wardhana; Jonny Syah R Purba; Ikawati Sulistyaningsih (Media Gizi Khatulistiwa, 2025)
Nutritional status is a measure of success in fulfilling nutrition in children as shown through weight achievement relative to age. The nutritional status of toddlers is very significant as a starting point for physical capacity in adulthood. Efforts to achieve a good nutritional status of children under five are inseparable from the role of parents, especially mothers as caregivers, because mothers as a person responsible for organizing family meals, including for children under five are very important. This study aims to find out the overview of the nutritional status of toddlers and maternal knowledge. The type of research used was descriptive research conducted on a sample of 35 people in July 2024 in Perapakan Village, Pemangkat District. Knowledge data was obtained by interviews using questionnaires and nutritional status data was obtained using weight and height measurements. The results of the study were obtained as many as 74.3% of the sample had less knowledge about the selection and processing of balanced nutritious food and as many as 25.7% of the sample had underweight nutritional status and 2.9% of the samples had undernutrition status and overnutrition status, respectively. There was a significant relationship between the level of knowledge and nutritional status of toddlers in the sample. It is necessary to carry out education about the selection and processing of nutritious and balanced foodstuffs.